2020
DOI: 10.3390/en13112832
|View full text |Cite
|
Sign up to set email alerts
|

Use of Alternative Raw Materials in Coke-Making: New Insights in the Use of Lignites for Blast Furnace Coke Production

Abstract: This paper presents the results of studies on the possibility of using lignite to produce blast furnace coke. The aim of the investigation was to evaluate the influence of lignite addition (direct addition or incorporated into briquettes) on the textural, structural and quality parameters (NSC-CRI and CSR) of blast furnace coke. It was found that the introduction of lignite in briquettes (4.5% addition) allows coke to be produced that is characterized by equally high NSC parameters as for coke obtained without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 57 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…Applying bio-based materials in metallurgical processes greatly impacts the total costs, energy consumption, operation stability, and, ultimately, final product quality. It is well known in the literature that biomass can be used in cokemaking [ 18 , 19 , 20 , 21 , 22 ], iron ore sintering [ 23 , 24 , 25 , 26 , 27 ], iron ore pellets production [ 28 , 29 ], and ironmaking [ 19 , 20 , 21 , 22 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Applying bio-based materials in metallurgical processes greatly impacts the total costs, energy consumption, operation stability, and, ultimately, final product quality. It is well known in the literature that biomass can be used in cokemaking [ 18 , 19 , 20 , 21 , 22 ], iron ore sintering [ 23 , 24 , 25 , 26 , 27 ], iron ore pellets production [ 28 , 29 ], and ironmaking [ 19 , 20 , 21 , 22 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used method is Sapozhnikov's method for determining plastic layer thickness [14,15], the less commonly used methods are Gieseler [16], the Audibert-Arnu dilatometer [17], and the Roga index [18]. In addition, the laboratory coking installation Karbotest is used to study the blend's properties and the coke quality [19,20]. When preparing the blend, carrying out a petrographic analysis of the blend components is required.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of bio-coal particle size on the quality of bio-coke, in terms of CRI and CSR values, is reported in the literature [23][24][25][26][27]. The addition of 0.3-5% [14], 2-5% [23,24], 5% [25], 2-10% [26], 8% [27], and 5-25% [28] charcoal or (4.5-9%) lignite [29] to the coking coal blend was studied. It was found that the CRI of bio-coke is higher in comparison to reference coke, and vice versa for CSR.…”
Section: Introductionmentioning
confidence: 99%